A study on the environmental aspects of a laundromat operation and the environmental responsibility of selected operators in Quezon City - Resurreccion, Rheena Buenviaje; Florendo, Racquel B. (Quezon City College of Home Economics, University of the Philippines, 2001)
In the last six years, Laundry Service Providers or more popularly known as Laundromats, are aggressively making their presence felt in Quezon City. From a non-existent industry it has transformed into a flourishing and promising business enterprise. The Laundromat with its operations naturally generates laundry wastes, and being part of a community, it should be able to function as it is designed to be while being environmentally friendly in all aspects of its operation. The study aimed to review and identify the specific rules and regulations applicable in the operation of a Laundromat. It tried to define the specific processes that give bearing to its over-all environmental impact. Lastly, it investigated the level of concern and general practices of selected Laundromat operators regarding the environmental impact of the system they are using. Content analyses were done to a number of DENR (Dept. of Environment & Natural Resources) and LLDA (Laguna Lake Development Authority) issuance's. These were the LLDA resolution Series of 1996 or the Environmental User Free System in the Laguna de Bay and DAO 35 or the Effluent Quality Standards, in particular. Twenty-eight (28) Laundromat Operators participated in this study. They answered a questionnaire that inquired about their practices in the operation of their installations. Percentage and frequency distributions were used to treat the data gathered. The results of the study showed that the government requires Laundromat Operations located in Quezon City to procure an LLDA Discharge permit and pay a user-fee before their effluents or liquid wastes could be legally allowed to drain to the Laguna de Bay. It follows that, the environment impact of a laundromat installation chiefly relies on processes that contribute to the quantity and quality of laundry wastes generated. Survey showed that franchisee operations enjoy tutelage and guidance from technical experts provided by either franchisers or exclusive suppliers, thus, they tend to be more systematized in their practices. Non-franchising or independent operators are lacking in this area and as a consequence, they are left to themselves at figuring out the best way to operate their systems. Although independent installations generate lesser amount of laundry wastes compared to franchisees, the different5 is not as significant, because both generate very large volumes of wastewater. Appallingly, majority or about 85% of all subjects do not have any wastewater treatment system and illegally dispose it directly down the drain. In fact, only four (4)_ of these Laundromats claim to have discharge permits. However, the researcher doubts the veracity of this claim because the level of treatment could not [possibly reach the effluent standards set by the DENR.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Laundry industry -- Philippines -- Quezon City -- Environmental aspects; Laundry industry -- Philippines -- Quezon City -- Waste disposal